Targeted Mutations Produce Divergent Characteristics in Pedigreed Sake Yeast Strains - Norapat Klinkaewboonwong; Shinsuke Ohnuki; Tomoya Chadani; Ikuhisa Nishida; Yuto Ushiyama; Saki Tomiyama; Atsuko Isogai; Tetsuya Goshima; Farzan Ghanegolmohammadi; Tomoyuki Nishi; Katsuhiko Kitamoto; Takeshi Akao; et al. (Microorganisms, 2023)
Modification of the genetic background and, in some cases, the introduction of targeted mutations can play a critical role in producing trait characteristics during the breeding of crops, livestock, and microorganisms. However, the question of how similar trait characteristics emerge when the same target mutation is introduced into different genetic backgrounds is unclear. In a previous study, we performed genome editing of AWA1, CAR1, MDE1, and FAS2 on the standard sake yeast strain Kyokai No. 7 to breed a sake yeast with multiple excellent brewing characteristics. By introducing the same targeted mutations into other pedigreed sake yeast strains, such as Kyokai strains No. 6, No. 9, and No. 10, we were able to create sake yeasts with the same excellent brewing characteristics. However, we found that other components of sake made by the genome-edited yeast strains did not change in the exact same way. For example, amino acid and isobutanol contents differed among the strain backgrounds. We also showed that changes in yeast cell morphology induced by the targeted mutations also differed depending on the strain backgrounds. The number of commonly changed morphological parameters was limited. Thus, divergent characteristics were produced by the targeted mutations in pedigreed sake yeast strains, suggesting a breeding strategy to generate a variety of sake yeasts with excellent brewing characteristics.